Exposure of Red Knots (Calidris canutus rufa) to Select Avian Pathogens; Patagonia, Argentina - D'amico, Veronica Laura; Bertellotti, Néstor Marcelo; Baker, Allan; Diaz, Luis Adrian (Journal of Wildlife Diseases)
As part of the shorebird surveillance, Red Knots (Calidris canutus rufa) were sampled in two Patagonian sites in Argentina, Rý´o Grande and San Antonio Oeste, during 2005–2006. Cloacal swabs and serum samples were collected from 156 birds and tested by virus isolation (Newcastle disease virus), polymerase chain reaction (PCR; avian influenza virus and Plasmodium/Hemoproteus), and for antibodies to St. Louis encephalitis virus. All test results were negative.Calidris canutus rufa) were sampled in two Patagonian sites in Argentina, Rý´o Grande and San Antonio Oeste, during 2005–2006. Cloacal swabs and serum samples were collected from 156 birds and tested by virus isolation (Newcastle disease virus), polymerase chain reaction (PCR; avian influenza virus and Plasmodium/Hemoproteus), and for antibodies to St. Louis encephalitis virus. All test results were negative. Fil: D'amico, Veronica Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Centro para el Estudio de Sistemas Marinos; Argentina Fil: Bertellotti, Néstor Marcelo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Centro para el Estudio de Sistemas Marinos; Argentina Fil: Baker, Allan. Royal Ontario Museum; Canadá Fil: Diaz, Luis Adrian. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto de Investigaciones Biológicas y Tecnológicas. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales. Instituto de Investigaciones Biológicas y Tecnológicas; Argentina